Mandibular reconstruction: a new defect classification system - G. T. Arotiba; J. T. Arotiba; B. O. Bamgbose; M. O. Gbotolorun; O. A. Taiwo; H. O. Olasoji (Nigerian Dental Journal)
This paper presents a new mandibular segmental defect classification system (La-Co-CE) with a view to highlight the complexity and difficulty of the reconstruction with free autogenous bone grafts which the most frequently used method for surgeons practicing in developing countries. We submit that defect classification systems will continue to remain relevant if surgeons are to is pre-operatively classify the envisaged operative difficulty and objectively compare the outcome postoperatively.